Peran Green Innovation Dan Modal Usaha Dalam Menentukan Sustainability Business UMKM Di Kabupaten Karawang - Nurhalimah, Nurhalimah; Yanti, Yanti; Lasmini, Lilis (Universitas Muhammadiyah Metro, 2023)
In the era of globalization, the country's economy is growing rapidly, especially in Indonesia, this is a challenge for each country to maintain the sustainability of the business. This study aims to examine how the role and application of Green Innovation and business capital in determining Sustainability Businesses. Taking the population in this study, namely SMEs in Karawang Regency, the number of samples is 100 respondents, using a purposive sampling method. The method applied in this research is using a questionnaire with a Likert scale of 1-5, this questionnaire is arranged in the form of a Google form. The analysis tool used is SmartPLS version 3.0. The stages of data analysis through three stages, namely Outer model, inner model analysis, and hypothesis testing. This research results that Green Innovation has a positive effect on Business Sustainability. Also, business capital has a positive effect on Business Sustainability.